Smart and sustainable cities through short supply chains of food - Santos, M. J. P. L. dos.; Baptista, N. (Proceedings of the 17th European Conference on Management Leadership and Governance (ECMLG 2021), 2021)
The world in general and cities in particular face tremendous challenges at the environmental, social, economic and institutional levels. Currently, cities need to be sustainable and smart. As our better knowledge, most of the literature explores the concept of smart cities from the point of view of information and communications technology unless the connection with the social and sustainability aspects remains unsolved. This paper tries to overcome this gap in the literature. The main aim is to analyse the contribution of short supply chains of foods in terms of the sustainability of smart cities. The methods include a scoping revision of the literature. Information and data also come from the preliminary results from the SGDsCONSUM project. The results confirm the positive impacts of short supply chains of food in urban areas towards smart and sustainable cities. The conclusions of this paper will be helpful for scholars and public decision-makers to implement their policies accordingly.